Meiji Japan and the imperial rule: a symbiotic encounter - Mansor Majdin, Mohamad Firdaus (Asian Scholars Network, 2022)
To speak of Meiji Ishin, one would normally come across many pieces of literature that mention the return of the Emperor to the centre of politics and administration in comparison to the previous Tokugawa administration (1603-1868). Yet one crucial question comes up from this is that as to why the Meiji insurgencies decided to bring the Emperor to the front and how this act would benefit their cause? In addressing such a crucial point, this paper attempts to revisit the essentiality of the Imperial factor in pushing forward the Meiji Ishin in the country during the 19th Century. It seeks to examine and investigate the motives that prompted the Meiji insurgencies to use the ‘imperial factor’ in their struggle in facing the Shogunate administration. In so doing, the study uses a method of content analysis to examine the significance of the ‘Imperial factor’ based on analysis of both Japanese and Western literature alike. The study suggests that Japanese Meiji insurgencies who later took up the charge of transforming Japan as a modern and strong nation-state economically and militarily must have realized that only with the support of the Japanese monarchy that this revolution could be strengthened and legitimized against the Shogunate forces and most importantly they could effectively push their reforms agenda in the country.